Women's rights in Asia and elsewhere – a fact or an illusion?. (4th May 2019) - Shah, D.
Abstract: More than one-third of the world's population resides in Asia. China and India have the largest population densities and the focus of this article is on these two countries. In the seventeenth century, women were globally treated as inferior and subordinate to men. Women had to listen to their fathers, husbands, and sons, and they could not inherit business or wealth. Starting in the eighteenth century and continuing in the nineteenth century, women's rights became central to political debates in Europe which demanded human rights, leading to the Women's Rights Movement. The Feminist movement began in the twentieth century, which focused on the reproductive rights of women. In the twentieth century, various Declarations have been signed by the United Nations to offer both gender equity and equality to women in the world, but unfortunately many of them have not been put into practice in Asia. In the twenty-first century, the feminist movement is focusing more on women having the power to decide the course of their lives. We still have to overcome challenges of unequal economic opportunity, political empowerment, gender violence, and human trafficking to achieve gender equality in Asia.